2018
DOI: 10.1002/cyto.a.23593
|View full text |Cite
|
Sign up to set email alerts
|

Morpho‐Functional Characteristics of Bone Marrow Multipotent Mesenchymal Stromal Cells after Activation or Inhibition of Epidermal Growth Factor and Toll‐Like Receptors or Treatment with DNA Intercalator Cisplatin

Abstract: This study is aimed to reveal morphological and functional changes in multipotent mesenchymal stromal cells (MSCs) isolated from the rat bone marrow after: (i) activation of Toll-like receptors (TLRs) with teichoic acid (TA), (ii) impact on epidermal growth factor (EGF) receptors with activator EGF or inhibitor Herceptin, and (iii) treatment with DNA intercalator Cisplatin. According to our results, TA and EGF cause an increase in the synthesis of glycosaminoglycans, c-Myc content, and protein in the MSC cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Studies on cervical epithelial cells based on Fourier Transform Infrared Spectroscopy (FTIR) suggested that for dysplastic and neoplastic changes, a characteristic decrease in the intensity of glycogen-specific bands was observed [37]. Glycogen is one of the compounds accumulated intracellularly in animal cells in the form of stores with a diameter of 10 to 40 nm [38]. Already in the 1930s, Schiller determined that cervical cancer cells, unlike healthy cells, lack glycogen [39].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cervical epithelial cells based on Fourier Transform Infrared Spectroscopy (FTIR) suggested that for dysplastic and neoplastic changes, a characteristic decrease in the intensity of glycogen-specific bands was observed [37]. Glycogen is one of the compounds accumulated intracellularly in animal cells in the form of stores with a diameter of 10 to 40 nm [38]. Already in the 1930s, Schiller determined that cervical cancer cells, unlike healthy cells, lack glycogen [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is impossible for me to ignore the actual political situation and the threat, cruelty and pain that our colleagues and friends, scientific authors (1,2), readership and their relatives and friends from Ukraine are facing now. I'm expressing my deep compassion to all of you, and I think I am writing here in the name of the majority of the worldwide cytometric and academic community.…”
mentioning
confidence: 99%